Endoscopic and Histologic Predictors of Outcomes in Pediatric Ulcerative Colitis-Caveat Emptor - Lorraine Stallard; Séamus Hussey; Séamus Hussey; Séamus Hussey (Frontiers Media S.A., 2021)
The impact of endoscopic and histological mucosal healing on outcomes in adult settings is impressive. Despite many clinical parallels, pediatric ulcerative colitis (UC) is set apart from adult disease in several respects. Many frequently used indices are not fully validated, especially in pediatric settings, and consensus on precise definitions in clinical settings are lacking. Endoscopic mucosal healing is an acceptable long-term treatment goal in pediatrics, but not histologic normalization. Early prediction of disease course in UC may allow treatment stratification of patients according to risks of relapse, acute severe colitis, and colectomy. Putative endoscopic and histologic predictors of poor clinical outcomes in adults have not held true in pediatric settings, including baseline endoscopic extent, endoscopic severity, and specific histologic characteristics which are less prevalent in pediatrics at diagnosis. In this mini-review we appraise predictive endoscopic and histologic factors in pediatric UC with reference to relapse, severe colitis, and colectomy risks. We recommend that clinicians routinely use endoscopic and histologic sores to improve the quality of clinical and research practice. The review summarizes differences between adult and pediatric prediction data, advises special consideration of those with primary sclerosing cholangitis, and suggests areas for future study in this field.